2021
DOI: 10.3390/su13094918
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Challenges and Opportunities for End-of-Life Vehicle Recycling in Developing Countries and Emerging Economies: A SWOT Analysis

Abstract: The importance of recycling end-of-life vehicles (ELVs) has been widely acknowledged as a means of reducing ELV waste to the environment. This reduced environmental waste contributes to achieving a number of UN SDGs, including the creation of sustainable cities. The recovery of secondary resources, such as metals, from the recycling of ELVs also reduces over-dependence on primary resources. This promotes efficient resource utilization and resource conservation. While recycling systems have been established and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…As a result, all new cars registered as of 2035 will be zero-emission [23]. Considering that the average age of vehicles in EU is 11.5 years, the end-of-life vehicle recycling policies become very important [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, all new cars registered as of 2035 will be zero-emission [23]. Considering that the average age of vehicles in EU is 11.5 years, the end-of-life vehicle recycling policies become very important [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Cars that are illegally dumped or abandoned in these countries are illegally collected by dealers for the recovery of re‐usable parts. However, improper handling results in leakage of hazardous materials to the soil and water, thereby contributing to environmental pollution [49] …”
Section: Pgms: Significance and Current Statusmentioning
confidence: 99%
“…Evaluation of EOL vehicle recycling data from some developing countries revealed that the lack of a regulatory framework for their management and recycling as well as access to relevant information is a common problem. [49] Certain liquids that are present in vehicles (e. g., motor and brake oil, antifreeze) have to be treated before disposal for removal of hazardous pollutants. Additionally, heavy metals found in vehicles, such as Hg, Pb, Cd, Cr, and Zn, need to be extracted properly to avoid soil and water contamination.…”
Section: Pgms: Significance and Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Numfor et al (2021) investigated the challenges and opportunities for ELV recycling in eight developing countries (Cameroon, Kenya, Nigeria, Egypt, India, Malaysia, Mexico, and South Africa), the study concluded that the greatest challenge encountered is poor policies and, in most cases, the absence of ELV management policy. This highlights the need to strengthen governance related to ELV management.…”
Section: Elv and Eol Lib Policies And Regulationsmentioning
confidence: 99%